Belangkas Robot As An Effort To Improve Calistung Ability In Early Children - Uci Rahmalisa; Arie Linarta; Sri Yulani (Universitas Islam Kuantan Singingi, 2022)
Education in the 4.0 era requires the education sector to be able to compete and utilize computer technology, which is currently developing rapidly as an interesting and interactive learning tool or media for children and to increase children's interest in learning. The first problem that came to the attention of the implementing team was that it was difficult for children to concentrate while studying, and children who entered elementary school without attending kindergarten still had difficulties in the processes of reading, writing, and arithmetic (Calistung), which of course would have an impact on children's delays in understanding learning material. The second problem is that the online teaching and learning process that was carried out previously was not effective in encouraging children's understanding of a lesson because it was difficult for children to focus on the learning being given. The third problem is that children are often exposed to gadgets that will have a negative impact on their gross and fine motor development. The duration of long and frequent use will lead to addiction to gadgets, the child's development will become less than optimal, and the child's emotions will be out of control and trigger early stress. The fourth problem is the absence of interactive learning media in partner schools that can increase children's interest in learning. The output target to overcome the existing problems will be interactive learning media in the form of a robot named BELANGKAS Robot (Concise Learning). The purpose of this research is to develop an alternative learning medium for children using robots by inviting children to collaborate and compiling a series of instructions for the robot to carry out a learning activity (an introduction to numbers, letters, and pictures) that leads to sharpening children's logical thinking and attracting children's interest in learning. reading, writing, and arithmetic. From the results of the research that has been done, the BELANGKAS robot is proven to be able to attract children's learning interest, and of course this interest will improve children's learning abilities, especially CALISTUNG.